Diversity of fauna species in Ayer Hitam Forest Reserve, Selangor, Malaysia - Ahmad Juffiry, Shahidin; Yusof, Ebil; Hussin, Mohamed Zakaria (Forestry Department Peninsular Malaysia, 2015)
Ayer Hitam Forest Reserve (AHFR) is one of the remaining lowland forest in the Klang Valley. A research was undertaken to study the fauna species in this forest. They were divided into four species groups namely; bird (nocturnal and insectivorous), bat, small mammal (non-volant) and primate. Each group used different capturing methods. Birds were trapped using Mist-netting method while bats were captured using both mist-net and harp-trap. Small mammal (non-volant) species were captured using live-trap. Distance Sampling Method for line transects and opportunistic surveys were used to observe primate species. A total of 7 species with 43 individuals of nocturnal bird and a total of 20 species of insectivorous bird with 146 individuals were captured. For bat, 10 species with 64 individuals were captured. Nine species with a total 62 individuals were recorded for small mammals. Only 4 species of primates were found in the AHFR out of a total 10 species present in Peninsular Malaysia.